Quota Enforcement in Resource Industries: Self-Reporting and Differentiated Inspections - Lars Gårn Hansen; Frank Jensen; Linda Nøstbakken (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2010)
Quotas or permits are frequently used in the management of renewable resources and emissions. However, in many industries there is concern about the basic e ectiveness of quotas due to non-compliance. We develop an enforcement model of a quota-regulated resource and focus on a situation with signi cant non-compliance and exogenous constraints on nes and enforcement budget. We propose a new enforcement system based on self-reporting of excess extraction and explicit di erentiation of inspection rates based on compliance history. In particular, we use state-dependent enforcement to induce rms to self-report excess extraction. We show that such system increases the e ectiveness of quota management by allowing the regulator to implement a wider range of aggregate extraction targets than under traditional enforcement, while ensuring an efficient allocation of aggregate extraction. In addition, inspection costs can be reduced without reductions in welfare.
Keywords: D61; H0; Q20; Q22; Q28; 330; Enforcement; Non-compliance; Self-reporting; Di erentiated inspections; Quotas; Emissions standards; Resource Management